Comparing the Main Anthropometric and Biomechanical Indexes in Male Adult Wushu Athletes in Taolu and Sanda Disciplines - azam daneshvar; Heydar Sadeghi (Islamic Azad University, Hamedan Branch, 2016)
Objective: The main aim of the study was comparing the main anthropometric and biomechanics indexes in elite male adult Wushu athletes in both Taolu and Sanda disciplines.  Methods: The sample of the present study included 20 elite male Wushu athletes who were checked for 33 anthropometric and 11 biomechanical indexes. The normality of the data was checked by Kolmogorov–Smirnov normality measure. Factor Analysis was run to determine the main indexes and independent samples .T-test was used at a significance level of p<0.05 to compare the means. Results: The results showed that in Taolu group, sitting height, waist to pelvic circumference ratio and body fat percentage were higher. Also, the weight, arm length, leg length, head circumference, arm circumference in contraction, shoulder width, the width of the wrist and body mass index were greater in the Sanda group. There was a meaningful difference between endurance indices, lower limb  muscular strength, semi dynamic balance in posterior-lateral direction, semi dynamic balance in right-anterior direction, semi dynamic balance in posterior-medial direction, semi dynamic balance in posterior-lateral direction (p<0.05).   Conclusion: There is a significant difference in the main anthropometric and biomechanical indicators of Wushu in both Taolu and Sanda disciplines. It appears that balance, endurance – strength of foot in the biomechanical properties are the most important Indicators in Taolu.